Role of Cinnamon Supplementation on Glycemic Markers, Lipid Profile and Weight Status in Patients with Type II Diabetes - Talaat, Sazan M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
Type II diabetes has been on the rise for the past few decades and the current management plan of diabetes is challenging to individuals in keeping their blood glucose levels within normal limits. There is a constant search of new ways to tackle these challenges. Cinnamon is suggested to have antihyperglycemic and lipid lowering effect and has been proposed to be utilized in type II diabetes. The aim behind this review is to explore the role of cinnamon in improving the glycemic status, lipid profile, and weight status of patients with type II diabetes. PubMed and ScienceDirect databases have been searched for eligible studies conducted until February 2022, the outcomes measured were glycemic markers as primary outcome and lipid profile and weight status as secondary outcomes. A total of ten trials involving 861 patients were included in the study. Five studies have demonstrated reductions in glycemic markers (ranging between −0.56 and −1.9 mmol/L for fasting blood sugar and between −0.21% and −0.93% for glycated hemoglobin) whereas the remaining four did not show any significant reduction. The most improvements in glycemic markers are seen in patients with poorly controlled diabetes and patients with higher body mass index (BMI) values. The majority of the studies did not record improvement in lipid profile. Changes in weight status are only observed in overweight patient category (BMI between 25 and 30). Overall, there is no coherent evidence to decide about antihyperglycemic, lipid lowering, and weight reducing effects of cinnamon in type II diabetes.